2014
DOI: 10.1002/jcp.24682
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide and C‐Type Natriuretic Peptide Maintain Porcine Oocyte Meiotic Arrest

Abstract: Recent studies have shown that C-type natriuretic peptide (CNP) serves as a key control system during mouse oocyte maturation. We used pig models (in vitro and in vivo) to explore the role played by the natriuretic peptide family in porcine oocyte maturation. We reported the expression and location of natriuretic peptide system in different stages of porcine antral follicles. Atrial natriuretic peptide (ANP) and CNP were expressed primarily in granulosa cells, whereas brain natriuretic peptide (BNP) and natriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 43 publications
5
51
4
Order By: Relevance
“…It appears that this is the first study showing that these three peptides have similar functions in same species. However, this contrasts with the effects of NPPA that have been reported in rats (Tornell et al, 1990), and of NPPC in mice (Zhang et al, 2010), as well as the effects of NPPB and NPPC that have been recently reported in pigs (Hiradate et al, 2013;Zhang et al, 2015), in which these peptides are essential for maintaining oocyte meiotic arrest. Initially, we observed that mRNA for NPPA, NPPC and their receptors (NPR-1, NPR-2 and NPR-3) were present in cumulus cells, and that in the bovine oocyte only mRNA for NPR-2 was present (Fig.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…It appears that this is the first study showing that these three peptides have similar functions in same species. However, this contrasts with the effects of NPPA that have been reported in rats (Tornell et al, 1990), and of NPPC in mice (Zhang et al, 2010), as well as the effects of NPPB and NPPC that have been recently reported in pigs (Hiradate et al, 2013;Zhang et al, 2015), in which these peptides are essential for maintaining oocyte meiotic arrest. Initially, we observed that mRNA for NPPA, NPPC and their receptors (NPR-1, NPR-2 and NPR-3) were present in cumulus cells, and that in the bovine oocyte only mRNA for NPR-2 was present (Fig.…”
Section: Discussioncontrasting
confidence: 74%
“…The natriuretic peptides (NPs) system consists of three endogenous peptides with high homology: NP precursor type-A (NPPA), type-B (NPPB) and type-C (NPPC), as well as three receptors (NPR-1, -2 and -3) that are located on NPPC is essential to block meiosis in mice (Zhang et al, 2010;Tsuji et al, 2012) and pigs (Hiradate et al, 2013;Zhang et al, 2015). Loss-of-function mutations in either NPPC or NPR-2 result in precocious resumption of meiosis in oocytes that are enclosed within antral follicles (Zhang et al, 2010;Tsuji et al, 2012;Geister et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…LH acts by lowering the levels of cGMP in the granulosa cells, thus reducing cGMP in the oocyte. Although this regulatory system is best understood in mice (Norris et al, 2009;Vaccari et al, 2009;Zhang et al, 2010;Kawamura et al, 2011;Tsuji et al, 2012;Geister et al, 2013), there is evidence that similar mechanisms operate in other mammals (Törnell et al, 1991;Peng et al, 2013;Hiradate et al, 2014;Zhang et al, 2014), including women (Kawamura et al, 2011;Liu et al, 2014). The LH-induced resumption of the meiotic cell cycle leads into a series of events by which the oocyte matures to become a fertilizable egg (Conti et al, 2012;Clift and Schuh, 2013;Holt et al, 2013;Mehlmann, 2013;Hunzicker-Dunn and Mayo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…LH signaling is known to decrease the amount of CNP in rat and mouse ovaries (Jankowski et al, 1997;Kawamura et al, 2011;Liu et al, 2014) and in human and porcine follicular fluid (Kawamura et al, 2011;Zhang et al, 2014); the decrease in the levels of CNP is associated with a decrease in Nppc mRNA (Kawamura et al, 2011;Tsuji et al, 2012;Liu et al, 2014). However, in the mouse ovary, where the kinetics are best characterized, the CNP decrease is first detected at 2 h Liu et al, 2014), whereas the decrease in cGMP is detected at 15 to 20 min (Norris et al, 2010;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridization was performed as described previously (Zhang et al, 2015). Briefly, ovaries with ovarian capsules were dissected from mice and were embedded in optimal cutting temperature (OCT) compound and frozen in liquid nitrogen until analysis.…”
Section: In Situ Hybridizationmentioning
confidence: 99%